The handbook of international crisis and risk communication research - Schwarz, Andreas, 1979-; Seeger, Matthew W. 1957-; Kim, Sora (Wiley-Blackwell, 2025)
"The second edition of the International Handbook of Crisis and Risk Communication Research, like the first edition, was based on the aspirational goal of continuing to expand, integrate, and internationalize the field. Issn this addition, we have included 50 chapters describing programs of research from around the globe, addressing diverse audiences, cultures, and risk/crisis types from a variety of methodological and disciplinary perspectives. A project of this scope and complexity simply could not be accomplished without the active support of others"-- Provided by publisher.
Keywords: Crisis management -- Handbooks, manuals, etc.; Risk communication -- Handbooks, manuals, etc.; Communication, International -- Handbooks, manuals, etc.; elektronické knihy; electronic books